Research of high strength steels bending - V. A. Tаmila; M. L. Nesterovich (Литьë и металлургия)
The article deals with the issues of obtaining high-strength steels. A conclusion about the effect of the temperature on the steel was drawn based on the research of the microstructure. To check the effect of the welding process on the steel under study, the hardness of the weld and the zone of thermal influence were measured. The weld was checked by X-ray television control for defects in the weld joint.To analyze the possibility of free bending with local heating experiments on tempering samples were conducted in order to identify its optimum temperature at which no cracking occurs in the steels after bending. Bending experiments were carried out after local heating.A comparison of the results of measuring the hardness of the weld, as well as samples obtained after tempering and local heating of the bending line were made. Graphs of the drop in hardness of the studied steel depending on the tempering temperature, as well as the drop in hardness as it moves away from the local heating line, are constructed. Bending experiments with compression of high-strength steels were performed using a substrate material.The samples obtained during the experiments were examined by X-ray for defects in the bending line. The value of compressive stresses acting on bent sample is calculated.